(untitled) (The Review of Diabetic Studies, 2024)
General health in Saudi Arabia is influenced by rapid socioeconomic changes, demographic shifts, and evolving disease patterns. Health workers play a key role in translating national health priorities into population-level outcomes. This article examines general health in Saudi Arabia, concentrating on the impact of health workers on health promotion, disease prevention, and system performance. Through a population health and workforce-centered approach, the paper highlights how healthcare professionals address non-communicable diseases, strengthen primary care, and improve health system performance. The analysis emphasizes the importance of investing in the health workforce to sustain improvements in overall health across the Kingdom.